Nephrolithiasis in hypercalcemic and normocalcemic primary Hyperparathyroidism - Vitorino Modesto dos Santos (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Primary hyperparathyroidism (PHPT) is a common condition  affecting  up  to  4  per 1000 of population,  and the  majority  of  cases  are  due  to  adenoma  or  hyperplasia  of the  gland  [1]. This endocrine  disorder  may  either  develop without  symptoms  or  be  classically  manifested  by  anorexia, nausea,  constipation,  polydipsia  and  polyuria  in  association with  hypercalcemia  [1].  Worthy  of  note  is  the  form  of  PHPT described in 2009 and characterized by normocalcemia, which persists  with  hypercalciuria,  nephrolithiasis  and  bone  loss in  the  majority  of  the  cases 1.  Nephrolithiasis  can  complicate 20%  of  hypercalcemic  and  18.2%  of  normocalcemic  PHPT;  moreover, calcium oxalate and calcium phosphate are the main components of the calculi [1]. Thiazide diuretics, lithium salt, immobilization,  and  inactivity;  in  addition  to  hyperoxaluria, hypocitraturia,  low  urinary  pH,  high  salt  ingestion,  and  low water intake play adverse roles [1]. Cinacalcet hydrochloride is a  calciomimetic  drug  that  can  activate  parathyroid  and  renal calcium-sensing receptors suppressing synthesis/ secretion of PTH, and  reducing  calcemia 1. This  drug  is  also  used  to  treat secondary  hyperparathyroidism  in  people  with  kidney  failure [1].